Analysis of attitudes and intentions of consumers towards the use of Internet banking services - Jovana Filipović (Anali Ekonomskog fakulteta u Subotici, 2020)
The main goal of this research is to determine the factors that influence the consumers` attitudes and intentions regarding the use of Internet banking. The conceptual model used in the research is a modified Technology Acceptance Model (TAM). In particular, the research analyzed the impact of perceived usefulness, perceived ease of use, trust and security and privacy on consumer attitudes towards internet banking, and also the impact of attitudes on intentions in consumer behavior. The results of the research indicate that perceived usefulness, perceived ease of use and safety and privacy have a positive and statistically significant impact on consumer attitudes, whereas trust has no statistically significant impact. In addition, the results show that consumer attitudes towards internet banking have a strong positive impact on consumers' intentions regarding their future behavior. Research represents a contribution to the existing scientific literature, but can also be of great importance to the management of banks, especially from the aspect of understanding the needs of potential users and increasing the number of users of these services.